Application of innovative pedagogical technologies in design education - Abdramanova Zh.M. , Abdramanova Zh.M. (Рroblems of engineering and professional education, 2022)
This article explains that each pedagogical technology has its own advantages and disadvantages. The maximum effect of using any technology can be achieved if necessary. The choice of specific forms and methods of training depends on the ultimate goal of training. The considered technologies are aimed at and contribute to the professional development of future designers.